Integrated design and operation assessment of a preheating system for liquid hydrogen fueled engines - Rompokos, Pavlos; Kang, Sangkeun; Roumeliotis, Ioannis (American Society of Mechanical Engineers (ASME), 2026)
Cryogenic liquid hydrogen (LH2) is highly considered as a potential long-term solution toward emissions reduction in the aviation sector. However, one of the major challenges that the handling and integration of the cryogenic fuel introduces is thermal management. In this paper, the design space exploration of an LH2 conditioning is presented to identify potential feasible solutions and limitations for its implementation. The preheating system comprises of secondary combustor that feeds a heat exchanger with hot gases to adequately supply the main engine with gaseous hydrogen at a constant temperature. The design space exploration addresses the heat exchanger design as well as the effect of retrofitting the system on kerosene-designed engines with different specific thrust. For performing the analysis, four baseline engine models and their equivalent integrated versions with the fuel preheating system have been created. Additionally, a framework for the sizing and off-design performance characterization of the heat exchanger is introduced. The integrated system performance across the design space is analyzed and a novel control strategy of the preheating system is proposed with the view of avoiding water vapor condensation of the hot gases of the preheating module. By applying this control, it was found that heat exchanger designs with lower effectiveness are less likely to lead to water condensation conditions and can adequately be supported with air sourced from the bypass duct without significant penalty in the overall energy efficiency of the engine.
Keywords: 40 Engineering; 7 Affordable and Clean Energy; Energy; 4001 Aerospace engineering; 4004 Chemical engineering; Design; Engines; Flow (Dynamics); Heat exchangers; Hydrogen; Temperature; Fuels